EFLECTIONS OF URARTIAN CITIES IN RURAL AREAS: POTTERS’ MARKS AND RED BURNISHED WARES FROM MURAT HÖYÜK AND MURAT TEPE IN BİNGÖL, TURKEY - Danışmaz, Harun; Özdemir, Abdulkadir (My University, 2022)
This study discusses previously unpublished examples of Urartian red burnished pottery and potters’ marks found during excavations at Murat Höyük and Murat Tepe in East Anatolia. Findings discussed in this study provide tangible evidence for the cultural influence of Urartian cities on rural areas. Murat Höyük and Murat Tepe are located on the northeast bank of the Murat River, at the point where the river meanders east. The two adjacent sites derive their name from this river. Excavations at Murat Tepe revealed two settlement levels dating to the Medieval Period and the Iron Age. At nearby Murat Höyük, Medieval, Middle Iron Age, Early Iron Age and Early Bronze Age levels were documented. A few examples of potters’ marks and red burnished ware sherds were found at both sites. In general, current research suggests that red burnished ware and ceramic vessels bearing potters’ marks were used in elite and palatial contexts in Urartian cities. Therefore, the attestation of these assemblages at rural sites such as Murat Höyük and Murat Tepe in a remote region away from Urartian cities, provides significant information on the kingdom’s cultural influence on rural areas.
Keywords: Arkeoloji; Tarih